P5 5 Meteor Mash - Blackburn, Benjamin William Edward; Soltysik, Milosz Jan; Swane, Joseph James (Physics Special Topics, 2023)
In this paper we calculated the kinetic energy of one of the meteors described in the spell 'Meteor Swarm' from D&D, and then estimated the crater that would be formed from it's impact. We found the kinetic energy to be 1.31x10^15J and the diameter and depth of the resulting crater to be 588m and 147 m respectively.